THE INFLUENCE OF E-WOM AND CORPORATE REPUTATION ON DOWNLOAD INTENTION - Budi Christanto; Caroline Fransisca; Kristin Nomleni; Michael Vikend Cu (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
One of the competent institutions for character development and human resource development is higher education. A higher education institution can be considered of high quality if it has the appropriate techniques in processing all supporting elements, including good coordination systems between the university and students, as well as between students and the university as a form of preparing human resources that can compete. Along with the development of time in supporting natural resource management and accompanied by rapid technological development, various alternative local applications have emerged according to the urgent needs in maximizing the performance of a company, especially in terms of coordination. Universitas Bunda Mulia itself has provided an application for users in the academic environment, specifically students. This research aims to determine the impact of EWOM and Corporate Reputation on the intention to download the Universitas Bunda Mulia application. The approach used in this research is quantitative with regression tests. Our target sample is Universitas Bunda Mulia students and alumni. The sampling technique we used is the convenience sampling method with multiple regression analysis as a data analysis method.